Adequacy of calcium intake during pregnancy in a tertiary care center - Chotboon C; Soontrapa S; Buppasiri P; Muktabhant B; Kongwattanakul K; Thinkhamrop J (Dove Medical Press, 2018)
Chokchai Chotboon,1 Sukree Soontrapa,1 Pranom Buppasiri,1 Benja Muktabhant,2 Kiattisak Kongwattanakul,1 Jadsada Thinkhamrop1 1Department of Obstetrics and Gynecology, Faculty of Medicine, Khon Kaen University, Khon Kaen, Thailand; 2Faculty of Public Health, Research Group on Prevention and Control of Diabetes in the Northeast, Khon Kaen University, Khon Kaen, Thailand Background: Calcium is an essential element for the body, which is taken through the dietary sources. Calcium supplements may be needed to achieve the dietary reference intake (DRI). Dietary calcium and supplemental calcium intake for calcium balance might be necessary. However, increasing evidence shows that calcium supplementation may enhance soft tissue calcification and cause cardiovascular diseases. Calcium requirement during pregnancy is markedly increased. If calcium supplementation depends on the dietary style of a region, then the adequacy of dietary calcium intake may guide the calcium supplementation. Materials and methods: A cross-sectional descriptive study was conducted among pregnant women who attended prenatal care at Srinagarind Hospital, Khon Kaen University. We used semiquantitative food frequency questionnaire (SFFQ) to evaluate the amount of daily calcium intake, and 3 days food record to assess the SFFQ reliability. We used the INMUCAL-N V.3.0, based on the Thai food composition table for nutritional calculation. Results: Among 255 recruited pregnant women, the mean daily dietary calcium intake was 1,256.9 mg/day (SD: 625.1) and up to 1,413.4 mg/day (SD: 601.3) in daily milk consumed group. Based on Thai DRI for pregnant women, with 800 mg/day as adequate intake of calcium, 74.9% had adequate calcium intake, and majority of them had milk daily. Conclusion: The majority of pregnant women in a province of Northeast Thailand had adequate calcium intake, particularly those who had milk with their meal every day. Keywords: calcium intake, pregnant women